STRATEGI KOMUNIKASI TERPADU DINAS KEBUDAYAAN DAN PARIWISATA KOTA SURAKARTA DALAM MENJAGA KELESTARIAN FOOD TRADITIONAL PADA SOLO INDONESIA CULINARY FESTIVAL - Adji Wijaya, Guntur; Hindra H, Nurnawati; Kusumo Aji, Haryo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The Surakarta City Tourism Office held a public activity to bring food and market food back to Surakarta City with a flagship programme called SICF (Solo Indonesia Culinary Festival). Through SICF 2023, all potential tourism supporters are developing. The consequences that must be carried out in the implementation of SICF 2023, the tourism and culture office of the city of Surakarta has difficulty if it organises internally so that it collaborates with stockholders and partners. one of the obstacles in organising SICF 2023 is in terms of integrated communication with all organising stockholders. the purpose of this research is to find out the planning, implementation and evaluation strategies of integrated communication carried out by the Surakarta Tourism Office and stockholders in organising SICF (Solo Indonesia Culinary Festival) 2023 as an effort to preserve traditional Solo food. In the process of conducting this research, data collection methods were carried out through interviews with informants. The informants selected were 4 people who were representatives of the tourism office, representatives of the Office of Cooperatives and MSMEs, representatives of the Industry and Trade Office and representatives of the Sinergi Semesta Event Organiser. Data were analysed and conclusions were drawn qualitatively without numbers. Data validity is proven by direct interactive with data sources (source triangulation). The conclusion shows that the successful implementation of SICF 2023 with the theme Ragam Cita Rasa Kuliner Nusantara was carried out by applying 4 main indicators, namely Defining the problem, Planning and programming, Taking action and communicating, and Evaluating the problem. SICF 2023 was successful and achieved its target visits and large transaction value. Keywords: Integrated Communication Strategy, SICF, Traditional Food and Culture and Tourism Office